Meningkatkan Produktivitas Checking Belt Variable Speed Dengan Optimalisasi Sistem Manajemen Informasi Dengan Metode Ahp, Use Case & UML (Studi Kasus Pt. Bando Indonesia) - Rahayu, Puji; Supono, Joko; Fachriansyah, Havid; Pratama, Ilham (Program Studi Teknik Industri Universitas Muhammadiyah Tangerang, 2024)
This research is motivated by data showing the productivity of monthly checking of variable speed belts by the finishing department which was only achieved 2 times during the 2021 period. For this problem, researchers conducted research aimed at increasing the results of checking variable speed belts. The objectives to be achieved in this study include: (1) Increase the productivity of the variable speed checking department. (2) Optimizing the existing information management system with the addition of automation features. (3) Knowing the results of the implementation of an information management system that has been optimized for the productivity of checking belt variable speed. The data used are primary data and secondary data. Decision making for improvement is made with the AHP method. System descriptions are done using UML. Analysis of the current system using use case diagrams and system testing using the black box method. The results showed a decrease in the time needed for the variable speed belt checking process from 7 minutes 21 seconds to 7 minutes 6 seconds, so that the checking results increased by 9.19% from an average of 6.91 S / M / H to 7.545 S / M / H. Keywords: Productivity, AHP, UML, use case, black box